An update on the management of breast cancer in Africa. Issue 1 (December 2017) - Vanderpuye, V.; Grover, S.; Hammad, N.; PoojaPrabhakar,; Simonds, H.; Olopade, F.; Stefan, D.
Abstract Background There is limited information about the challenges of cancer management and attempts at improving outcomes in Africa. Even though South and North Africa are better resourceds to tackle the burden of breast cancer, similar poor prognostic factors are common to all countries. The five-year overall Survival rate for breast cancer patients does not exceed 60% for any low and middle-income country (LMIC) in Africa. In spite of the gains achieved over the past decade, certain characteristics remain the same such as limited availability of breast conservation therapies, inadequate access to drugs, few oncology specialists and adherence to harmful socio-cultural practices. This review on managing breast cancer in Africa is authored by African oncologists who practice or collaborate in Africa and with hands-on experience with the realities. Methods A search was performed via electronic databases from 1999 to 2016. (PubMed/Medline, African Journals Online) for all literature in English or translated into English, covering the terms "breast cancer in Africa and developing countries". One hundred ninety were deemed appropriate. Results Breast tumors are diagnosed at earlier ages and later stages than in highincome countries. There is a higher prevalence of triple-negative cancers. The limitations of poor nursing care and surgery, inadequate access to radiotherapy, poor availability of basic and modern systemic therapies translate into lower survival rate. Positive strides in breast cancer management in Africa include increased adaptation of treatment guidelines, improved pathology services including immuno-histochemistry, expansion and upgrading of radiotherapy equipment across the continent in addition to more research opportunities. Conclusion This review is an update of the management of breast cancer in Africa, taking a look at the epidemiology, pathology, management resources, outcomes, research and limitations in Africa from the perspective of oncologists with local experience.